2021
DOI: 10.3390/ijms22136868
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Regulate Sialylations of N-Glycans, Affecting Cell Migration and Survival

Abstract: N-Glycosylations are an important post-translational modification of proteins that can significantly impact cell function. Terminal sialic acid in hybrid or complex N-glycans has been shown to be relevant in various types of cancer, but its role in non-malignant cells remains poorly understood. We have previously shown that the motility of human bone marrow derived mesenchymal stromal cells (MSCs) can be modified by altering N-glycoforms. The goal of this study was to determine the role of sialylated N-glycans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…The regulatory effects of cytokines on glycosylation enzymes are examined in limited studies and are poorly understood and controversial. For example, IFN-γ increases sialylated N-glycan structures due to upregulated mRNA levels of sialyltransferases (ST6GAL1) in human bone marrow-derived mesenchymal stromal cells (MSCs) to influence migration and survival ( 52 ). However, another study reported that IFN-γ decreased the expression of ST6GAL1 in LPS-induced B cell cultures ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory effects of cytokines on glycosylation enzymes are examined in limited studies and are poorly understood and controversial. For example, IFN-γ increases sialylated N-glycan structures due to upregulated mRNA levels of sialyltransferases (ST6GAL1) in human bone marrow-derived mesenchymal stromal cells (MSCs) to influence migration and survival ( 52 ). However, another study reported that IFN-γ decreased the expression of ST6GAL1 in LPS-induced B cell cultures ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…ST3Gal-4 involvement in cancer cell migration processes was previously described. However, except for stem/stromal cell biology, its role in cell survival remains not wellestablished (Guerrero et al, 2020;Templeton et al, 2021). Our results suggest that targeting ST3Gal-4 sialyl transferase in the context of CTCL could represent another strategy to induce tumor cell death.…”
Section: Discussionmentioning
confidence: 87%
“…Our results suggest that targeting ST3Gal-4 sialyl transferase in the context of CTCL could represent another strategy to induce tumor cell death. However, alternative therapeutic drugs are necessary because current inhibitors of sialyltransferase are not ST3Gal-4 specific and may have therefore important side effects (Templeton et al, 2021). These unexpected effects include an increase in tumor cell survival as observed in human multiple myeloma cells (Natoni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Both Ac 5 ManNTProp and Ac 5 ManNTBut, which display thiol groups on the cell surface, were found to suppress adipogenic differentiation in hADSCs, but they did not interfere with differentiation to a glial lineage ( Du et al, 2021 ). Moreover, both osteogenic and adipogenic differentiation were inhibited, when MSCs were pre- or continuous treated with 3F-Neu5Ac ( Templeton et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cells enhanced trophic factor release by optimizing stiffness of the polymer coating, which reduced the required number of cells through augmenting the efficacy of each NPC. On the other hand, supplementation with 3F-Neu5Ac was found to improve adhesion and elevate the rate of migration of MSCs, thereby promoting their survival in an in vitro ischemia model ( Templeton et al, 2021 ). In summary, MGE can effectively modulate cell biological behaviors ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%